2022
DOI: 10.1038/s41467-022-31825-z
|View full text |Cite
|
Sign up to set email alerts
|

Stomatin modulates adipogenesis through the ERK pathway and regulates fatty acid uptake and lipid droplet growth

Abstract: Regulation of fatty acid uptake, lipid production and storage, and metabolism of lipid droplets (LDs), is closely related to lipid homeostasis, adipocyte hypertrophy and obesity. We report here that stomatin, a major constituent of lipid raft, participates in adipogenesis and adipocyte maturation by modulating related signaling pathways. In adipocyte-like cells, increased stomatin promotes LD growth or enlargements by facilitating LD-LD fusion. It also promotes fatty acid uptake from extracellular environment … Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
10
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 17 publications
(11 citation statements)
references
References 75 publications
1
10
0
Order By: Relevance
“…Even so, in accordance with in vitro research with contradicting findings, it was found that sustained adipogenesis would decrease if ERK was activated because peroxisome proliferator-activated receptor (PPAR)γ expression can be inhibited by prolonged stimulation of the sustained activation through MAPK40-mediated phosphorylation [33] .…”
Section: Resultsmentioning
confidence: 67%
“…Even so, in accordance with in vitro research with contradicting findings, it was found that sustained adipogenesis would decrease if ERK was activated because peroxisome proliferator-activated receptor (PPAR)γ expression can be inhibited by prolonged stimulation of the sustained activation through MAPK40-mediated phosphorylation [33] .…”
Section: Resultsmentioning
confidence: 67%
“…Similarly, Wu et al. found that inhibiting the STOM gene increased ERK1/2 phosphorylation while reducing PPARγ expression and lipid accumulation in 3T3‐L1 cells 42 . Liu et al.…”
Section: Discussionmentioning
confidence: 93%
“…41 Similarly, Wu et al found that inhibiting the STOM gene increased ERK1/2 phosphorylation while reducing PPARγ expression and lipid accumulation in 3T3-L1 cells. 42 Liu et al discovered that F I G U R E 6 Exploring the mechanism of CPM-regulated BMSC differentiation. (A) Principal component analysis (PCA) shows transcriptome heterogeneity of BMSCs between the CPM knockdown group (siCPM) and control group (siNC).…”
Section: Discussionmentioning
confidence: 99%
“…The lipid elevation concerns cholesterol rather than triglycerides, although the latter correlate positively with chemerin in metabolic disorders [ 33 , 34 ]. Both in vivo and in vitro studies have shown that chemerin promotes lipid uptake and storage, evidenced by the enhanced production of PPARg [ 35 ], adiponectin [ 36 ], p-ERK1/2 [ 37 39 ], and FABP4 [ 40 ]. In HTR-8/SVneo trophoblast cells, chemerin increased cholesterol biosynthesis by upregulating SREBP2 [ 41 ], while it diminished LDL endocytosis via downregulation of both the LDLR and SORT1 [ 42 , 43 ].…”
Section: Discussionmentioning
confidence: 99%